2022
DOI: 10.1111/os.13212
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Alignment of Patients with Basilar Invagination: A Radiological Study

Abstract: Objective: To investigate the cervical alignment and the relative range of motion (ROM) in patients with basilar invagination (BI).Methods: A total of 40 BI cases (38.1 years old AE 17.9 years old, 19 male and 21 female) and 80 asymptomatic individuals (33.8 years old AE 10.8 years old, 40 male and 40 female) were included. The Skull-C 2 /Skull-BV, Skull-C 7 , C 2 -C 7 /BV-C 7 wall angles, C 0 -C 2 /C 0 -BV, C 0 -C 7 , C 1 -C 7 , and C 2 -C 7 /BV-C 7 angles were measured in dynamic X-ray images (including neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Due to the prolapse of odontoid into the foramen magnum, the medulla oblongata and spinal cord are compressed which result in neural symptoms in BI patients. The BI patient was found to present a stiffer neck [ 6 ]. We deduced that the BI patient needed to maintain their cervical spine in a certain posture to reduce discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the prolapse of odontoid into the foramen magnum, the medulla oblongata and spinal cord are compressed which result in neural symptoms in BI patients. The BI patient was found to present a stiffer neck [ 6 ]. We deduced that the BI patient needed to maintain their cervical spine in a certain posture to reduce discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results indicated that functional muscles were less in BI patients and decreased with age with more obvious trends than control group. Furthermore, our previous study also revealed that BI patients presented the loss of cervical curvature [ 6 ]. Therefore, early exercise on both cervical extensor and flexor muscles is necessary to alleviate fatty infiltration and strengthen muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations